Bioenergetic dysfunction in a zebrafish model of acute hyperammonemic decompensation - Zielonka, Matthias; Probst, Joris; Carl, Matthias; Hoffmann, Georg F.; Kölker, Stefan; Okun, Jürgen G. (Experimental neurology, 2019)
Acute hyperammonemic encephalopathy is a life-threatening manifestation of individuals with urea cycle disorders, which is associated with high mortality rates and severe neurological sequelae in survivors. Cerebral bioenergetic failure has been proposed as one of the key mechanisms underlying hyperammonemia-induced brain damage, but data supporting this hypothesis remain inconclusive and partially contradictory. Using a previously established zebrafish model of acute hyperammonemic decompensation, we unraveled that acute hyperammonemia leads to a transamination-dependent withdrawal of 2-oxoglutarate (alpha-ketoglutarate) from the tricarboxylic acid (TCA) cycle with consecutive TCA cycle dysfunction, ultimately causing impaired oxidative phosphorylation with ATP shortage, decreased ATP/ADP-ratio and elevated lactate concentrations. Thus, our study supports and extends the hypothesis that cerebral bioenergetic dysfunction is an important pathophysiological hallmark of hyperammonemia-induced neurotoxicity.
Gesehen am 27.03.2019